PENGARUH SARI TEBU DALAM PEMBUATAN MORTAR TRADISIONAL UNTUK PENANGANAN KEBOCORAN CANDI PAWON - Ari Swastikawati; Leliek Agung Haldoko; Pramudianto Dwi Hanggoro; Arif Gunawan (Borobudur, 2022)
Pawon Temple has the potential for weathering problems due to weather factors. Rainfall and temperature fluctuations trigger various damage and weathering. Rainwater that enters the stone grout on the roof of the temple can cause the surface of the walls and chambers of the Pawon Temple to become moist, and trigger the growth of microorganisms that will cause wear and tear on the walls of the temple. Therefore, conservation efforts are needed on the roof of the Pawon Temple to reduce the infiltration of rainwater into the body of the Pawon Temple. This study aims to determine the correct composition of traditional mortar to prevent leakage by covering the grout on the roof of Pawon Temple. The research method chosen is descriptive qualitative. The addition of sugarcane juice can reduce the saturated water content in the mortar. Mortar with the addition of sugarcane juice can reduce porosity. Mortar with a ratio of 2 sand: 1 brick powder: 1 lime and with the addition of sugarcane juice produces the best mortar with the highest compressive strength but with the lowest porosity.